PERANCANGAN ULANG ALAT UJI FATIGUE ROTARY BENDING - Clementinus Benny Agung Pambayu; Agustinus Purna Irawan; Didi Widya Utama (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Fatigue is a form of failure that occurred in the structure due to fluctuating dynamic loads that occur below the yield strength for a long time and repeatedly. Determines the required material fatigue test equipment fatigue. Fatigue test equipment is designed with rotary bending systems. Re-design tool that was originally done to digitize readings manually replaced with a digital readout. Digitization include the addition of pulse digital meter, digital meter counter and the system auto shutdown. The addition of a digital readout to facilitate the conduct of research and testing of materials.